2021
DOI: 10.2147/ppa.s277965
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hair Concentrations of Antiretrovirals with Virologic Outcomes Among People Living with HIV in Guangxi, China

Abstract: Background: Hair concentrations of antiretrovirals are an innovative and non-invasive method for measuring cumulative antiretroviral exposure and assessing long-term antiretroviral adherence. This study aimed to examine hair concentrations of antiretrovirals in relation to virologic outcomes among PLHIV in Guangxi, China. Methods: Cross-sectional data of hair concentrations of antiretrovirals and HIV viral load were collected from 215 PLHIV in Guangxi, China. Multivariate logistic regression analyses were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…This study found that hair zidovudine concentrations are closely associated with virologic suppression as indicated by the significant intergroup difference and correlations between them. The intergroup difference was also observed in our previous study, 24 illustrating that PLWH showing high hair zidovudine concentrations due to adequate ARV adherence may have more access to virologic suppression. Furthermore, hair zidovudine concentrations gave prediction power matching with, but slightly weaker than hair lamivudine concentrations.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This study found that hair zidovudine concentrations are closely associated with virologic suppression as indicated by the significant intergroup difference and correlations between them. The intergroup difference was also observed in our previous study, 24 illustrating that PLWH showing high hair zidovudine concentrations due to adequate ARV adherence may have more access to virologic suppression. Furthermore, hair zidovudine concentrations gave prediction power matching with, but slightly weaker than hair lamivudine concentrations.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, we reported that hair zidovudine concentrations had a similar effect on predicting virologic suppression as hair lamivudine concentrations did and were much better than self-reported measures. To the best of our knowledge, while no association between hair zidovudine concentrations and virologic outcomes was reported in our previous study with small-size participants, 24 we further characterized the strong prediction of hair zidovudine concentrations on virologic outcomes among a large-scale cohort of Chinese PLWH. The results indicated that hair zidovudine concentrations might be an alternative biomarker of virologic outcomes consistent with the verified hair lamivudine concentrations.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations